TEACHERS’ VOICES IN WORDWALL MEDIA APPLICATION IN TEACHING YOUNG LEARNERS CONTEXT: A NARRATIVE INQUIRY - Insani, Afra Nadya Putri; Romadhon, M Galuh Elga; Heriyawati, Dwi Fita (University of Kuningan, 2024)
Teacher of English Young Learner must be aware the students need in their learning, especially on using online media learning. Many researchers were conducted research on utilizing online media, Wordwall. It is an online based game tool. This research was aimed to investigate teacher’s voice in Wordwall media application in teaching young learners. This research used narrative inquiry. This research analyzed the teacher’s perception on using Wordwall media. There is a lack of study on teacher of English Young Learner’s perception of Wordwall.net as the media in learning vocabulary, despite the fact that numerous research studies have examined the usage of web tools connected to vocabulary and perception of Wordwall. This research was only structured interviewed the teacher of English Young Learner in one of the Elemantary school of Malang. The collected data then described. The study found that teachers had positive perceptions of using Wordwall to learn vocabulary. Teachers found it to be a useful tool for assessing student learning. The study concluded that Wordwall is a valuable tool for vocabulary learning. It is engaging, fun, and effective in improving learning outcomes.